Mating behaviour of ram on exposure to estrous ewes - PATEL, M; DAS, N; PANDEY, H N; YADAV, M C; P S, GIRISH (The Indian Journal of Animal Reproduction, 2007)
The experiment was conducted to study the pattern of rams’ mating behaviour and its preference for ewe when exposed to multiple estrous ewes. Four rams and four estrous ewes were used for the study. Ewes were shorn and brought to estrus artificially. Different mating activities were noted during one hour mating session. The number of times ewe mated and time spent by ram with ewe were also noted to check the order of preference among the available ewes. Courtship activities were found low with subsequent ejaculation. Depending upon percentage of mounting sessions, number of mounts per session, number of matings per session and time spent by ram with each ewe; the ewes were ranked I, II, III & IV by allotting marks to each parameter. Ewes A, B, C & D ranked I, II, IV & Ill indicating the preferential mating by the ram among available ewes. It was observed that number of ewes mated per session varied and ram’s preference was based on number of times the ewe served and varied from estrus to estrus of the same ewe. It was concluded that preferential mating of rams was found among available estrous ewes, which led to uneven distribution of mating. The number of mounts per hour and ejaculation per hour increased when ewe number in the mating pen increased.